Epidemiologi Dan Diagnosis Preeklamsia - Rahmatullah, Muhammad Rayza; Sutarto, Sutarto; Sari, Ratna Dewi Puspita; Romulya, Ari Irawan (Medula, 2024)
Preeclampsia is a serious pregnancy complication characterized by high blood pressure and organ damage. This condition poses a health risk for both the mother and the fetus. This article reviews the epidemiology and diagnosis of preeclampsia. Its epidemiology is complex with varying global prevalence. Risk factors include maternal age, history of preeclampsia and family, multiple pregnancies, obesity, diabetes, and kidney disease. Common diagnostic methods include blood pressure measurement, urine analysis, laboratory tests, and Doppler ultrasonography to assess the placenta and fetus. Prevention and early detection are the major priorities to reduce maternal and infant mortality rates. Further research is needed to develop better diagnostic and prevention strategies. Increasing understanding of the epidemiology and diagnostic methods of preeclampsia, more mothers and babies can be protected from the risks of this condition in the future.